Understanding the properties and functional role of neutrophils in oral squamous cell carcinoma – A systematic review - Thayalan Dineshkumar; Nirmala Anandan; Krishnan Rajkumar; Indumathi N (Oral Oncology Reports)
Background: OSCC, the most prevalent type of oral cancer, is thought to be caused by genetic alterations and is more common in people who use tobacco products, alcohol, betel quid, and areca nuts. Even with all of the breakthroughs in treatment, late diagnosis raises concerns about survival. This leads to the ongoing development of novel prognostic indicators. Recent years have seen a notable advancement in the study of cancer with the introduction of neutrophils as a prognostic indicator of overall survival, disease-free survival, and disease-specific survival. Aims and objectives: The current study aims to review the role of neutrophils in oral cancer and thus evaluate the prognostic role of neutrophils. Methods: A literature search was done in various electronic databases, and the data were extracted according to the predefined criteria. Original studies of 28 records were included in the analysis. Results: Twenty-eight prospective and retrospective studies were included in this systematic review. All the included studies showed that neutrophils play a crucial role in cancer progression and the prognosis of the patient. The analyses showed that neutrophils play a significant role in adverse OS, DFS, and DSS in HNSCC, which can serve as a cost-effective prognostic biomarker to help stratify patients and individualize treatments. Conclusion: The findings reported here show that neutrophils are crucial to the biology of cancer. Neutrophils come into direct contact with tumor cells very early in the development of tumors because they are quickly recruited. The “crosstalk” that occurs between tumor cells and neutrophils prolongs the life of the leukocytes and promotes their hyperactivity. The findings of our investigation clearly show that neutrophils are involved in OSCC.